Bioinformatics of Genome Regulation and Stucture - edited by Nikolay Kolchanov, Ralf Hofestaedt, Luciano Milanesi (Springer (India) Private Limited, 2004)
Bioinformatics of Genome Regulation and Structure covers: -regulatory genomic sequences: databases, knowledge bases, computer analysis, modeling, and recognition; -large-scale genome analysis and functional annotation; -gene structure detection and prediction; -comparative and evolutionary genomics; -computer analysis of genome polymorphism and evolution; computer analysis and modeling of transcription, splicing, and translation; structural computational biology: structure-function organization of genomic DNA, RNA, and proteins; -gene networks, signal transduction pathways, and genetically controlled metabolic pathways: principles of organization, operation, and evolution; -data warehousing, knowledge discovery and data mining; and, -analysis of basic patterns of genome operation, organization, and evolution. The data presented may be used while solving a wide range of problems, both basic and applied, in various directions of molecular biology, molecular genetics, biotechnology, pharmacogenetics, pharmacology, and adjacent fields of medicine, veterinary, and agrobiology.
Includes bibliographical references (p. [343]-370) and index.
Keywords: Genomics -Mathematical models. Genomics-Data processing. Bioinformatics